The inflammatory potential of the diet is prospectively associated with subjective hearing impairment. (30th September 2020) - Andreeva, V A; Péneau, S; Julia, C; Shivappa, N; Hébert, J R; Wirth, M D; Touvier, M; Hercberg, S; Galan, P; Kesse-Guyot, E
Abstract: Background: Age-related hearing loss is prevalent yet insufficiently addressed by public health research. Subjective hearing loss has been highlighted as a key determinant of reduced quality of life, while chronic low-grade inflammation is an established determinant of adverse age-related outcomes. To our knowledge, this study was the first to investigate the link between the inflammatory potential of the diet and hearing loss. Methods: We prospectively studied 3, 435 French adults enrolled in the SU.VI.MAX (1994-2002) and SU.VI.MAX 2 (2007-2009) cohorts. The inflammatory potential of the diet was estimated by the Dietary Inflammatory Index (DII) using established methodology and repeated, baseline 24-h dietary records. Subjective hearing impairment was assessed after a median of 12 years by 3 Yes/No items and by a composite score, dichotomized for analyses. We fit multivariable logistic regression models adjusted for pertinent covariates. Results: Compared to men, women exhibited higher DII (more pro-inflammatory diet) and less hearing impairment (both p < 0.0001). Given significant interaction results, sex-specific models were fit. Among men, a significant positive association between DII (continuous scale) and inability to follow a conversation in a noisy place was found (OR = 1.10; 95% CI: 1.02, 1.18), while the inverse association was seen among women (OR = 0.92; 95% CI: 0.87, 0.98). Regarding the need to turn up the volume on the television/radio, a significant positive association with DII (continuous scale) was found only among men (OR = 1.09; 95% CI: 1.01, 1.18). The only significant association with the composite score of subjective hearing loss was found among women, when modeling DII as quartiles (OR Q3 vs Q1=0.74; 95% CI: 0.57, 0.97). Conclusions: The findings among men support the hypothesis that a pro-inflammatory diet could increase risk of age-related hearing loss, whereas the findings among women were unexpected and merit further investigation. Key messages: Given rapid population aging worldwide, there is an urgent need for public health research on modifiable risk factors of hearing impairment. The role of diet in hearing impairment is complex and likely sex-specific; a pro-inflammatory diet might be a risk factor for hearing impairment, especially among men.